STUDI DESKRIPTIF PRAKTEK KERJA INDUSTRI KOMPETENSI KEAHLIAN DESAIN KOMUNIKASI VISUAL - Anah Anah; Puspa Djuwita (Manajer Pendididikan, 2019)
The purpose of this study was to know the description of the planning Practice the Working Industrial in Design Communication Visual, the implementation Practice the Working Industrial in Design Communication Visual, and Practice the Working Industrial in Design Communication Visual of vocational High School 5 of Bengkulu. The methode of this research is a qualitative descriptive study. The subjectts of this research were principals, vice principals, students and taechers at Vocational High School 5 of Bengkulu, and DU/DI (user), using data collection techniques such as observation, interview and documentation study, analyzed using with reduction, data presentation, and conclusion. The results showed that (1) planning has been implemented fairly well starting from the curriculum, work program, prakerin administration, financing, socialization, and student counselor teacher, (2) implementation of prakerin runs properly but some obstacles are found such as students having difficulties when operating new tools, lack of time discipline, and (3) evaluation have been undertaken by prakerin activity providers ranging from assesment, student reports to evaluation.